Coats' disease: An Indian perspective - Rishi, Pukhraj (Medknow Publications, 2010)
AIM: To describe the clinical features, treatment and outcome patterns in 307 eyes with Coats' disease. MATERIALS AND METHODS: Retrospective chart review of patients diagnosed with Coats' disease between January 1996 and January 2006 from a single referral center in southern India. RESULTS: Two hundred and eighty patients (307 eyes) with mean age of 15.67 years (range: Four months-80 years) were included. Decreased vision (77%), unilateral affection (90%) and male preponderance (83.4%) were chief presenting features. Anterior segment involvement was seen in 67 (21.8%) eyes. Retinal telangiectasia were seen in 302 (99%) eyes, exudation in 274 (89%) eyes and retinal detachment in 158 (51.5%) eyes. Four-quadrant disease was seen in 207 (67.2 %) eyes. Visual acuity was < 20/200 in 249 (80.9%) eyes. One hundred and nine of 176 treated eyes (61.93%) had favorable anatomical outcome; 207 of 280 eyes (74%) had an optimal structural outcome. Seventeen (5.3%) eyes were enucleated. Complications following treatment included phthisis bulbi (7%), neovascular glaucoma (5%), epiretinal membrane (4.4%) and rubeosis iridis (4.4%). CONCLUSION: Indian patients with Coats' disease have a high male predominance, the majority of whom present with severe visual impairment and extensive four-quadrant exudation. Unusual presentations such as pain, vitreous hemorrhage and a high incidence of anterior segment involvement are distinctive to Indian eyes.